Genomic affinities in Turnera (subseries Turnera, Turneraceae) inferred by in situ hybridization techniques - López, Alicia (2010)
Subseries Turnera comprises a polyploid complex with ploidy levels ranging from diploid (2n = 2x = 10) to octoploid (2n = 8x = 40). The use of fluorescent in situ hybridization greatly improved the knowledge of the karyotypes of Turnera species by detecting and mapping rDNA sites. Interspecific variability in the number of sites was detected, but not in correlation with the ploidy level. A chromosome pair with a strong hybridization signal was always visible and this signal corresponded to the secondary constriction detectable by conventional techniques. Genomic in situ hybridization experiments combined with information on meiotic pairing in species and interspecific hybrids revealed that homologies detected by molecular analysis are greater than those detected by chromosome pairing. This suggests that the formation of the allopolyploids could involve species more closely related than previously assumed. Despite the molecular affinity among the genomes, the meiotic pairing is probably controlled by specific genes that restrict homeologous pairing in polyploids.